Advanced diffusion processes and phenomena - Öchsner, Andreas; Murch, Graeme; Belova, Irina (Diffusion and defect data. Defect and diffusion forum ;, 2014)
This topical volume on Advanced Diffusion Processes and Phenomena addresses diffusion in a wider sense of not only mass diffusion but also heat diffusion in fluids and solids. Both diffusion phenomena play an important role in the characterization of engineering materials and corresponding structures. Understanding these different transport phenomena at many levels, from atomistic to macro, has therefore long attracted the attention of many researchers in materials science and engineering and related disciplines. The present topical volume captures a representative cross-section of some of the.